2013
DOI: 10.1016/j.cognition.2013.08.016
|View full text |Cite
|
Sign up to set email alerts
|

Authentic Gettier cases: A reply to Starmans and Friedman

Abstract: Do laypeople and philosophers differ in their attributions of knowledge? Starmans and Friedman maintain that laypeople differ from philosophers in taking 'authentic evidence' Gettier cases to be cases of knowledge. Their reply helpfully clarifies the distinction between 'authentic evidence' and 'apparent evidence'. Using their sharpened presentation of this distinction, we contend that the argument of our original paper still stands.We would like to thank Starmans and Friedman (this issue) for their careful re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…They also tentatively report being unable to find any difference between ethnic groups in their sample of participants (for additional discussion, see Starmans & Friedman and Nagel et al. ; for further evidence on epistemological thought experiments, see Turri, Buckwalter, & Blouw, ; Powell, Horne, & Pinillos, ; Powell, Horne, Pinillos, & Holyoak, ; for evidence of cross‐cultural variation in intuition in other areas of philosophy, see Abarbanell & Hauser, ; Haidt, Koller, & Dias, ; Machery, Mallon, Nichols, & Stich, ; Machery, Olivola, & De Blanc, ; Machery et al., ).…”
Section: Introductionmentioning
confidence: 96%
“…They also tentatively report being unable to find any difference between ethnic groups in their sample of participants (for additional discussion, see Starmans & Friedman and Nagel et al. ; for further evidence on epistemological thought experiments, see Turri, Buckwalter, & Blouw, ; Powell, Horne, & Pinillos, ; Powell, Horne, Pinillos, & Holyoak, ; for evidence of cross‐cultural variation in intuition in other areas of philosophy, see Abarbanell & Hauser, ; Haidt, Koller, & Dias, ; Machery, Mallon, Nichols, & Stich, ; Machery, Olivola, & De Blanc, ; Machery et al., ).…”
Section: Introductionmentioning
confidence: 96%
“…(answer options: "yes" or "no"). 2 Nagel et al(2013b) argue that the distinction between Apparent and Authentic Evidence cases is far from being well-defined and clear-cut and that there are several possible understandings of it. For the sake of this paper, I propose to employ the understanding fleshed out at the beginning of this section.…”
Section: K1 (Controlmentioning
confidence: 99%
“… 6 The third premise is also dubious, however. In two recent studies involving skeptical hypotheses, Jennifer Nagel (2012) and her team (Nagel et al 2013) found no statistically significant correlations between ethnicity, philosophical training, and knowledge ascriptions. Moreover, the majority of respondents in Nagel's studies found it intuitive to deny knowledge when unrealized skeptical possibilities were mentioned.…”
mentioning
confidence: 98%